Efektivitas Pelaksanaan Program Pengembangan Usaha Mikro Kecil Dan Menegah Usaha Mikro Kecil Menengah) ( Suatu Studi Di Dinas Koperasi, Usaha Mikro, Kecil. Dan Menegah Kota Manado) - Suryaningrum, Kania; Pangkey, Masje; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract:This research aims to know and observe the implementation of the program of development ofmicro small medium by the cooperatives, micro, small, and medium-sized city of manado. an increase inhuman resources of micro-entrepreneurs, small and medium enterprises are also very limited. Thus thisgreatly affects the performance of the Department of cooperatives and micro small medium manado wellin data retrieval and processing of data. enterprise development for micro, small and medium enterprisesappear to have been hampered due to lack of capital and also the soul of entrepreneurship(enterpreneurship). This is due to the lack of a partnership effort with the banks and State-ownedenterprises. the factors that cause this internally caused from employees of HR Department ofcooperatives and micro small medium manado city is still limited, especially in terms of mastery ofaccounting cooperative. This needs to be there is special training for employees to master the accountingcooperative so that information will not experience difficulties. external factors that emerged was the lackof human resource capacity of the micro, small and medium enterprises.The research methods used in this study is a qualitative method, with the techniques of primaryand secondary data collection performed by the library studies and fieldwork (interviews, observation anddocumentation studies). as for the respondents/informants of this research is the Head Office of microsmall and medium city of manado: 3 sub field of micro small and medium enterprises: 6 peopleperpetrators of micro enterprises small and medium-sized city of manado. with the data analysistechniques in reduction of data, data presentation, and conclusion and verify the withdrawal.The results showed that the effectiveness of the implementation of the program of development ofmicro, small, and medium (micro small medium-sized) (a study in the Department of cooperatives andmicro small medium manado) in measure of concept by gibson (1984), namely the production, efficiency,customer satisfaction, adaptation, and development. In view of these five aspects, namely the production,efficiency, customer satisfaction, adaptation, and development of almost everything said has not beengoing well. These are all proven to be due to the utilization of human resources in the Department is stillminimal. Additionally in terms of funding for the capital in a given community micro small medium is stillvery minimal as well. In the management of the loan capital is also very difficult and very convoluted belit.Referring to the discussion and the conclusions above suggest then. in order for the Departmentof cooperatives and micro small medium city of manado in the efficiency of implementing the developmentprogram of micro small medium to medium small micro-businessmen should be based on a sense ofresponsibility to improve the welfare of the principal micro small medium and not for the personal benefitof a certain group or bureaucracy. Department of cooperatives and micro small medium manado moreinternal organization, i.e. fix by doing makeovers, engage actors micro small medium to be more willing touse the Department of cooperatives and micro small medium city of manado as a training and learning interms of entrepreneurship. and provide satisfying service for your principals micro small medium. in orderfor the Department of cooperatives and micro small medium manado city is more closer to the principalsof small medium and micro enterprises can carry out the program to its full potential. and in this case alsorequired the importance of good teamwork and a fellow co-worker that compact implementation of theobjectives to be achievedkey words: effectiveness of program implementation the development of micro, small, and mediumenterprises